Establish a Digital Real-Time Learning System With Push Notifications - Wu, Hsin-Te (Frontiers in Psychology, 2022)
This study proposes a push notification system that combines digital real-time learning, roll-call, and feedback collection functions. With the gradually flourishing online real-time learning systems, this research further builds roll-call and feedback functions for students to enhance concentration and provide opinions. Additionally, the lecturers can do a roll call irregularly and randomly through the push notification function, avoiding students logging in but away from the keyboard. Lecturers can also send questions to a specific student or invite all students to answer; the replies can show students’ learning performance. The system will store each notification in a database and analyse messages automatically to record roll calls. Moreover, the system can record the time and intervals of student feedback, enabling lecturers to check students’ attention and learning conditions. Currently, most online digital systems depend on the lecturer to be responsible for the entire system; taking a roll call and asking questions will consume the lecturer’s teaching time and strength. The system developed in this article can do roll calls and feedback by push notifications, reducing lecturers’ workload. Furthermore, the roll-call and automatic record functions can save the time of paperwork after a course.